Strategies for solar and wind integration by leveraging flexibility from electric vehicles: The Barbados case study. (1st December 2018) - Taibi, Emanuele; Fernández del Valle, Carlos; Howells, Mark
Abstract: Rapid deployment of large shares of Variable Renewable Energy (VRE) is driving a shift in economics and operational practices in power systems around the world, creating the need for a more flexible and decentralized power system. In this context, electric vehicles (EVs) are expected to play a significant role, as they can make use of large shares of renewables in the power system to decarbonise the transportation sector. It is important to carefully plan for EV integration to make sure that they facilitate the integration of VRE and capture the potential benefits for the power system. This paper assesses the different impacts on production costs that electric vehicles could have depending on different charging profiles and considering the value added from allowing the EVs to provide energy and ancillary services to the grid. This paper shows how smart charging strategies can 1) limit the total increase in production cost from charging EVs, 2) facilitate VRE integration into the system reducing curtailment 3) affect marginal cost of electricity and 4) reduce the investment needed for grid connected storage, using an innovative approach to calculate the contribution of EVs to system reliability based on the different charging scenario. Finally, the effects of adding a constraint to represent battery degradation due to operation are analysed. This analysis is carried out using as a case study the Caribbean island of Barbados, given the expected large shares of VRE in the future, however it suggests a general framework to assess the impact of EVs in power systems with high shares of VRE. Highlights: Smart charging of EVs can facilitate integration of large shares of VRE. Smart charging of EVs can reduce incremental generation cost and VRE curtailment. V2G can reduce electricity and ancillary services prices. Innovative approach to model V2G in PLEXOS. Degradation of EV batteries when feeding into grid is key to assess V2G viability.